2014
DOI: 10.1039/c4cc06016d
|View full text |Cite
|
Sign up to set email alerts
|

A DNA aptamer to c-Met inhibits cancer cell migration

Abstract: The HGF/c-Met pathway is known to play a key role in cancer metastasis. CLN0003_SL1, a 50-mer DNA aptamer that binds to the c-Met protein, was found to inhibit HGF-induced c-Met activation. This aptamer could suppress cancer cell motility in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 20 publications
5
114
0
Order By: Relevance
“…The aptamer CLN3 is the only known c‐met‐binding DNA aptamer. The minimal binding domain of CLN3, SL1, was found to retain high binding affinity for c‐met and blocked the HGF/c‐met interaction and c‐met signaling in SNU‐5 cells . In this study, we demonstrate that SL1 has high specificity and affinity to membrane‐bound c‐met in MM.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The aptamer CLN3 is the only known c‐met‐binding DNA aptamer. The minimal binding domain of CLN3, SL1, was found to retain high binding affinity for c‐met and blocked the HGF/c‐met interaction and c‐met signaling in SNU‐5 cells . In this study, we demonstrate that SL1 has high specificity and affinity to membrane‐bound c‐met in MM.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to binding cellular c‐met, we found that SL1 possesses tumour inhibitory activity. Ueki et al reported that SL1 inhibits metastasis‐related behaviour, such as the scattering and migration of SNU‐5 cells . Similarly, Piater et al described a truncated version of CLN3 (CLN3‐T) that suppressed HGF‐induced migration of NCI‐H441 cells and invasion of MDA‐MB‐231 cells and inhibited c‐met phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] The functions of RTKs are mainly determined by ligand-dependent receptor dimerization and autophosphorylation to initiate downstream signaling cascades. AD -CID nanodevice is composed of two subunits,asensor (S)and an actuator (A), hooking on the extracellular region of c-Met via the specific aptamer, [11] generating two DNA-based chimeric receptors (Figure 1a;s ee also the Supporting Information, Figure S1). AD -CID nanodevice is composed of two subunits,asensor (S)and an actuator (A), hooking on the extracellular region of c-Met via the specific aptamer, [11] generating two DNA-based chimeric receptors (Figure 1a;s ee also the Supporting Information, Figure S1).…”
mentioning
confidence: 99%
“…[11] Based on the finding that homodimers of c-Met aptamers can activate c-Met, [12] Ueki and co-workers recently proposed an intriguing approach to redefine the ligand specificity of c-Met to other targets by using bi-specific aptamers to form at arget/dual-aptamer ternary complex. [11] Based on the finding that homodimers of c-Met aptamers can activate c-Met, [12] Ueki and co-workers recently proposed an intriguing approach to redefine the ligand specificity of c-Met to other targets by using bi-specific aptamers to form at arget/dual-aptamer ternary complex.…”
mentioning
confidence: 99%